Effectiveness of LI4 and SP6 Acupressure on Labor Pain Reduction and Positive Childbirth Experience During the Active Phase of the First Stage of Labor - Nasution, Yulia Fatma; Yaumil Fauziah; Annisa Namirah Nasution; Dessy Elvira; Rayi Al Hay Surahman; Zahwa Aulia Barata Lubis, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Background: Labor pain is a major challenge during childbirth that can negatively affect maternal satisfaction and labor outcomes. Acupressure is a sustainable complementary therapy that can be integrated into midwifery practice to support positive childbirth experiences. Objectives: This study aimed to examine the effectiveness of acupressure at LI4 and SP6 sites in reducing labor pain and enhancing positive childbirth experiences during the active phase of first-stage labor. Methods: A one-group pretest-posttest quasi-experimental study was conducted in Medan involving 30 laboring women selected through purposive sampling. Pain severity was measured using the Numeric Rating Scale (NRS), and childbirth experiences were evaluated using a structured questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The mean labor pain score significantly decreased from 8.10 ± 0.85 before intervention to 5.30 ± 1.04 after intervention. Concurrently, maternal satisfaction and childbirth experience scores significantly increased after acupressure therapy ($p < 0.001$). Conclusions: Acupressure at LI4 and SP6 points effectively reduces labor pain and improves childbirth experiences. As a low-cost and sustainable intervention, it should be integrated into routine maternity care to support positive childbirth experiences.